Non‐invasive assessment of liver fibrosis in chronic viral hepatitis. (2nd November 2015) - Orasan, Olga H.; Iancu, Mihaela; Sava, Madalina; Saplontai‐Pop, Aniela; Cozma, Angela; Sarlea, Simina Tarmure; Lungoci, Corneliu; Ungureanu, Marius‐Ionut; Negrean, Vasile; Sampelean, Dorel; Dumitrascu, Dan Lucian
Abstract: Background: Hyaluronic acid (HA), ASAT to Platelet Ratio Index (APRI), ASAT/ALAT ratio, Fibrosis 4 score (FIB4) and FibroScan were studied as non‐invasive markers of liver fibrosis (F) in chronic viral hepatitis B (CHB) and C (CHC), in an attempt to avoid the complications of liver puncture biopsy, considered the gold standard in the evaluation of F. The aim of our research was to study whether HA, APRI, ASAT/ALAT ratio, FIB4 and FibroScan are useful non‐invasive markers in predicting severe F in Romanian patients. Patients and Methods: This was a prospective multicenter transversal and observational study, which included 76 patients with CHB/CHC. The independent effect of studied markers was tested using multiple binary logistic regression. Results: In patients with CHB and CHC, the APRI cut‐off value for F4 was 0·70 ng/mL (Se = 77%, Sp = 78%), the FIB4 cut‐off value was 2·01 (Se = 77%, Sp = 69%), and the FibroScan cut‐off value was 13·15 (Se = 92%, Sp = 88%). For patients with CHB/CHC, there was a significant linear positive correlation between F and HA ( r = 0·42, P = 0·001), FibroScan ( r = 0·67, P < 0·001), APRI ( r = 0·46, P < 0·001) and FIB4 ( r = 0·51, P < 0·001). Considering age, sex and body mass index as possible confounding factors or covariates in multivariable logistic modelling, FibroScan was the unique test that able to significantly highlight the presence of F4 score in CHB/CHC patients ( P = 0·009) while FIB4 test seems to have a tendency to statistical significance. Conclusion: FibroScan, APRI and FIB4 are useful non‐invasive tests for the evaluation of F4 in patients with CHB and CHC.